2021
DOI: 10.1111/jen.12899
|View full text |Cite
|
Sign up to set email alerts
|

Attraction of the biocontrol agent, Lema praeusta, towards two Commelinaceae weed volatiles

Abstract: Two Commelinaceae weeds, Commelina benghalensis L. and Murdannia nudiflora (L.) Brenan, are abundant in rice fields of India. Larvae and adults of Lema praeusta (Fab.) (Coleoptera: Chrysomelidae) voraciously consume these two weeds. Synthetic herbicides are applied to control both weeds, but applications of these substances have harmful effects in environment and beneficial organisms. So, it is necessary to use native biocontrol agent to control these weeds. Hence, an attempt has been made to find volatile org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Implicating feeding by caterpillars of D. indica resulted in qualitative as well as quantitative changes in VOCs among volatiles of insect-damaged plants in comparison to volatiles of undamaged plants. 29,35 Methyl salicylate was detected as HIPVs in ID MNS and ID BAR plants but not in ID POLO plants. Nerol was an unique HIPV in ID MNS plants.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Implicating feeding by caterpillars of D. indica resulted in qualitative as well as quantitative changes in VOCs among volatiles of insect-damaged plants in comparison to volatiles of undamaged plants. 29,35 Methyl salicylate was detected as HIPVs in ID MNS and ID BAR plants but not in ID POLO plants. Nerol was an unique HIPV in ID MNS plants.…”
Section: Discussionmentioning
confidence: 92%
“…The results of the present study on the olfactory responses of D. indica adults revealed that virgin females and gravid females had similar behavioral response to volatiles of undamaged T. anguina plants, which indicates that the response to host plant volatiles is not associated with the physiological state (mating status) of the female. 30,35,39 Therefore, we used virgin D. indica females throughout the olfactory bioassays. However, olfactory responses of virgin and gravid females could be different when volatiles from undamaged plants were tested against volatiles from conspecific-damaged plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the treatment of mechanical damage (MD), 10 leaves of a plant were wounded twice with hole punches (each hole 0.5 cm), and volatile blends were collected without delay after wounding. An experimental plant was positioned in a closed glass dome (4 L) with Te on base having a small opening for passing the stem of plant (Das et al 2021) (Supplementary Fig. S1).…”
Section: Plant Volatile Blend Collectionmentioning
confidence: 99%